2006
DOI: 10.1007/s10750-005-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Limnological Conditions on Clostridium Botulinum Type E Presence in Eastern Lake Erie Sediments (Great Lakes, USA)

Abstract: Avian and fish botulism outbreaks have been recorded since 1999 in eastern Lake Erie. These outbreaks are caused by Clostridium botulinum type E, a toxin-producing bacteria that is found in anoxic substrates rich in organic material. We studied the environmental conditions present in eastern Lake Erie during 2002, a year when several botulism outbreaks were observed. We also tested for the presence of C. botulinum type E in lake sediments. Samples were taken at six stations from two sites of different depths i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…Bacterial (Mycobacterium avium [29] and Clostridium botulinum type E [19]), protozoan (Cryptosporidium species [22]), and viral (enterovirus [EV] [5,13,15], hepatitis A virus [HAV] [6,14], and rotavirus [6]) pathogens have been detected in environmental sediments. Whittington et al reported previously that M. avium in sediments from a dam lake survived 12 to 26 weeks longer than it did in a water column (29).…”
mentioning
confidence: 99%
“…Bacterial (Mycobacterium avium [29] and Clostridium botulinum type E [19]), protozoan (Cryptosporidium species [22]), and viral (enterovirus [EV] [5,13,15], hepatitis A virus [HAV] [6,14], and rotavirus [6]) pathogens have been detected in environmental sediments. Whittington et al reported previously that M. avium in sediments from a dam lake survived 12 to 26 weeks longer than it did in a water column (29).…”
mentioning
confidence: 99%
“…BoNT/E outbreaks in the Great Lakes region typically occur between June and December and correlate with low mean annual water levels and increased surface water temperatures (25). It has been hypothesized that BoNT/E is mobilized through Great Lakes aquatic food webs consisting of exotic species (19,25,32,33), providing a potential link between sediment-inhabiting clostridia and the intoxication of fish-eating birds. Using the BoTest Matrix E assay to conduct enhanced epidemiological investigations of avian BoNT/E outbreaks, including the analysis of aquatic food web components, would aid in our understanding of toxin mobilization pathways and provide critical insights for the management and conservation of bird species in the Great Lakes region.…”
Section: Fig 6 Quantification Ofmentioning
confidence: 99%
“…This is supported by the isolation of Clostridium botulinum from fish muscle and alimentary canal tissues as well as detection of the BoNT/E gene in fish liver and intestine samples collected within the Great Lakes Basin (8,16,47). Additional studies have identified the BoNT/E gene in sediment samples collected from Lake Erie, suggesting that sediment ingestion is a route for bacterial infection or toxin accumulation in bottom-feeding fish or bottom-dwelling invertebrates such as filter-feeding dreissenid mussels (32,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased water temperatures may enhance the type E detection in sediment, potentially indicating bacterial growth under anoxic conditions (9,19,26). In addition, other physicochemical parameters such as redox potential, pH, salinity, available phosphorus, and turbidity may contribute to C. botulinum type E growth (19,27,28). Relationships among these parameters are complex; a multivariate regression model developed using various sediment and water variables indicated that type C outbreak risk increased with 7.5 to 9.0 pH, negative redox potential, Ͼ20°C water temperature, and Ͻ2.0 ppm salinity (29).…”
mentioning
confidence: 99%